GRAMMATICAL METAPHOR IN PAN BALANGTAMAK: SYSTEMIC FUNCTIONAL LINGUISTICS PERSPECTIVE - I Ketut Suardana (Denpasar Institute, 2020)
This paper analyses the application of grammatical metaphor in Pan Balang Tamak text. The text originates spoken text that has existed in Balinese community. The text is rewritten into written text in Balinese language. This paper analyzes the application of grammatical metaphor in Pan Balang Tamak text. The theory which is used to analyze is the theory Systemic Functional Linguistics proposed by Halliday (1994) and supported by other theories. The method used to find data was qualitative, library research. The data were taken from the text written by (Supatra, 2014). The result of the research suggests that the text employ small number of grammatical metaphor. Ideational grammatical metaphor was hired in the text such as: transitivity, Process + Range. The function of grammatical metaphor in the text indicated that the text of Pan Balang Tamak was categorized as spoken text. Interpersonal grammatical metaphor suggested that Pan Balang Tamak use variation of expressions which were used to refuse Jero Klian’s claim politely